Effect of Pomegranate Juice on the Manufacturing Process and Characterization of Feta-Type Cheese during Storage. (29th November 2020) - Lashkari, Hannan; Varidi, Mohammad Javad; Eskandari, Mohammad Hadi; Varidi, Mehdi
Abstract : The present research aimed to produce Fruit Feta-type cheese and investigate the effects of pomegranate juice on the manufacturing process and characterization of Feta-type cheese during storage. In order to produce Feta-type cheese with pomegranate juice, part of the milk was replaced with pomegranate juice. Therefore, it was necessary to produce Feta-type cheese with whey-less method, which is a good substitute for ultrafiltrated cheese. Initially, whey-less Feta-type cheese was produced. The formula was optimized based on the physicochemical characteristics of the marketed ultrafiltrated Feta cheeses. At the optimal point, the amount of cream, MPC, WPC, and fresh milk were 45.6, 11.7, 2.7, and 40%, respectively. Whey-less Feta-type cheese with these ratios was produced and the effects of different levels of pomegranate juice (0, 5, 10, 15, and 20%) on its physicochemical, textural, microbial, and sensorial properties during 60 days of storage were studied. The results showed that pomegranate juice increased acidity, total phenol, anthocyanin, DPPH inhibition, and a ∗ value, and reduced the pH, peroxide value, thiobarbituric acid (TBA), proteolysis, lipolysis, and L ∗ and b ∗ values. Adding pomegranate juice to cheese reduced all of the textural indices except the adhesiveness. Sensory evaluation of the samples showed that the sample containing 20% of pomegranate juice had a higher score and was selected as the best sample.